PVDF (Polyvinylidene Fluoride) adhesive power improving accelerant and preparation method thereof
Through scientific proportioning and composite technology, combined with the advantages of modified polyacrylonitrile and modified polyimide, PVDF adhesion enhancement accelerator is prepared, which solves the limitations of PVDF adhesion enhancement in traditional methods, and achieves the improvement of energy density and cycle stability of lithium-ion batteries.
Patent Information
- Application Number
- CN202411870639.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional methods have limitations when improving the adhesion of PVDF, such as increased processing difficulty and poor toughness of polyimide adhesives, which leads to prone to cracking when the lithium-ion battery pole sheet is curled.
Through scientific proportioning and composite technology, combined with the advantages of modified polyacrylonitrile (PAN) and modified polyimide (PI), a PVDF adhesion enhancement accelerator is prepared to achieve a significant increase in adhesion to PVDF, while reducing the amount of PVDF used in lithium-ion batteries.
It significantly improves the adhesion of PVDF, reduces the amount of PVDF, improves the energy density and cycle stability of lithium-ion batteries, and improves the overall performance of the battery.
Smart Images

Figure BDA0005195675960000081
Abstract
Description
Technical Field
[0001] The present application relates to the field of lithium-ion battery adhesives, and in particular to a PVDF adhesion enhancing promoter and a preparation method thereof. Background Art
[0002] With the rapid growth of the new energy vehicle and portable electronic device markets, the performance requirements for lithium-ion batteries are becoming increasingly stringent. As a key component of battery electrodes, the adhesion performance of PVDF binder is directly related to the overall performance of the battery. However, traditional methods of improving PVDF adhesion have limitations, such as increased processing difficulty caused by increasing molecular weight. Other widely studied binders are polyimide binders. Traditional polyimide binders are mainly prepared using dianhydride and diamine as raw materials, but traditional polyimide binder materials have the problem of poor toughness, which makes the pole piece prone to cracking when curled.
[0003] Therefore, it is particularly important to develop a new type of promoter that can effectively improve adhesion while taking into account economy and processing convenience. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present application provides a PVDF adhesion enhancing promoter and a preparation method thereof. The promoter prepared in the present application cleverly combines the advantages of modified polyacrylonitrile (PAN) and modified polyimide (PI), and achieves a significant improvement in the adhesion of PVDF through scientific proportioning and composite technology. At the same time, it effectively reduces the amount of PVDF used in lithium-ion batteries, thereby improving the energy density and cycle stability of the battery.
[0005] In the first aspect, the present application provides a PVDF adhesion enhancing accelerator, which adopts the following technical solution: A PVDF adhesion enhancing accelerator is prepared by raw materials including modified polyacrylonitrile, modified polyimide and a high-efficiency solvent, wherein the mass ratio of the modified polyacrylonitrile to the modified polyimide is 1:0.2-2, and the high-efficiency solvent is selected from at least one of N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide.
[0006] By adopting the above technical scheme, modified polyacrylonitrile (PAN) and modified polyimide (PI) as the main components in this application play a key role in improving the adhesion of PVDF (polyvinylidene fluoride). Modified polyacrylonitrile (PAN): PAN has excellent mechanical strength, chemical stability and easy processability. As the core component of the adhesion promoter, it significantly improves the adhesion of PVDF through interaction with PVDF. PAN forms stable chemical bonds in PVDF, enhancing the bonding strength and durability of the material. The synergistic effect between PAN and modified PI is the key to this application. Through scientific proportioning and composite technology, PAN and modified PI interact to further improve the adhesion of PVDF. This synergistic effect comes not only from the interaction between the two, but also from their interaction in lithium-ion batteries, thereby achieving a significant improvement in the adhesion of PVDF, while effectively reducing the amount of PVDF used in lithium-ion batteries and improving the energy density and cycle stability of the battery. Modified polyimide (PI): PI has excellent heat resistance, insulation and mechanical strength. As a reinforcing component, it further enhances the adhesion of PVDF through interaction with PAN. PI forms stable chemical bonds in PVDF, improving the heat resistance and mechanical strength of the material, thereby improving the overall performance of the battery. The heat resistance and mechanical strength of PI combined with the adhesion properties of PAN achieve a significant improvement in adhesion to PVDF. This synergistic effect not only improves the bonding strength and durability of PVDF, but also improves the performance of lithium-ion batteries, such as energy density and cycle stability. High-efficiency solvents (such as N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide): used to dissolve and mix PAN and PI to form a uniform polymer solution. These solvents have good solubility and chemical stability, and can effectively dissolve PAN and PI, thereby facilitating subsequent processing and application. High-efficiency solvents play an important role in the dissolution and mixing of PAN and PI. They not only provide good solubility, but also help form a uniform polymer solution, thereby ensuring the uniform distribution of PAN and PI in PVDF and improving adhesion. In summary, this application achieves a significant improvement in the adhesion of PVDF through the scientific ratio and composite technology of PAN and modified PI. The synergistic effect between PAN and PI, as well as the role of efficient solvents in the dissolution and mixing process, jointly improve the amount of PVDF used in lithium-ion batteries and the performance of the batteries. This innovative preparation method and material combination provides an effective solution for improving the adhesion of PVDF and optimizing the performance of lithium-ion batteries.
[0007] Preferably, the mass ratio of the modified polyacrylonitrile to the modified polyimide is 1:0.6.
[0008] By adopting the above technical scheme, modified polyacrylonitrile (PAN) and modified polyimide (PI) as two polymer materials play an important role in the preparation of PVDF adhesion promoter. The mass ratio of PAN and modified PI is 1:0.6, which is obtained through scientific experiments and optimization, aiming to achieve the maximum improvement of PVDF adhesion. PAN and modified PI have different chemical structures and characteristics. PAN is mainly composed of hydrocarbons and has good mechanical strength and chemical resistance, while PI contains aromatic rings and imide structures and has excellent heat resistance and mechanical properties. Through reasonable proportioning, the advantages of the two materials can be complementary, thereby improving the adhesion of PVDF. PAN and modified PI will interact during the composite process, such as hydrogen bonds, van der Waals forces, etc. These interaction forces can enhance the bonding strength of the two materials, thereby improving the adhesion of PVDF. The interfacial compatibility of PAN and modified PI is also an important factor affecting the adhesion of PVDF. By modifying PI, it can be better compatible with PAN, thereby improving the adhesion of PVDF. In summary, the mass ratio of PAN to modified PI of 1:0.6 is the optimal ratio obtained through scientific experiments and optimization in the preparation of PVDF adhesion promoter, which can achieve a significant improvement in PVDF adhesion.
[0009] Preferably, the modified polyacrylonitrile is prepared from raw materials, in parts by mass: 80-90 parts of a first monomer, which is at least one of acrylonitrile and methacrylonitrile; 0-15 parts of a second monomer, which is at least one of an acrylate and a methacrylate monomer; 0-5 parts of a third monomer, which is a combination of one or more of an olefin acidic monomer, a sodium salt corresponding to an olefin acidic monomer, or a lithium salt corresponding to an olefin acidic monomer; and an emulsifier, deionized water and an initiator, wherein the emulsifier is sodium dodecyl sulfate; and the initiator is ammonium persulfate.
[0010] Preferably, the second monomer is a combination of one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methacrylate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, methoxypolyethylene glycol methacrylate and ethoxyethyl acrylate; the third monomer is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
[0011] Preferably, the preparation method of the modified polyacrylonitrile comprises the following steps: (1) Pre-emulsification: the first monomer, the second monomer, and the third monomer are uniformly mixed, and then an emulsifier and deionized water are added to pre-emulsify to obtain a mixed emulsion; (2) heating the pre-emulsified mixed emulsion in step (1) to the reaction temperature and stirring the reaction, adding an initiator dropwise for 1 hour, and keeping the temperature for 4 hours to obtain a preliminary emulsion; (3) filtering, neutralizing, and cooling the preliminary emulsion obtained in step (2) to obtain a polymer emulsion; (4) drying the polymer emulsion obtained in step (3) to obtain a solid powder; (5) The solid powder obtained in step (4) is washed, purified, dried and sieved to obtain modified polyacrylonitrile.
[0012] Preferably, the preparation method of the modified polyimide comprises the following preparation steps: S41, under nitrogen protection, the amino-terminated silicone oil, diisocyanate and N,N-dimethylformamide are mixed, and the polymerization reaction is carried out at 25-60° C. for 4-10 hours to obtain a prepolymer; S42, polymerizing the prepolymer with anhydride monomer and diisocyanate at 90-100° C. for 6-12 hours to obtain modified polyimide.
[0013] By adopting the above technical scheme, the preparation method of modified polyimide includes two steps, which is intended to synthesize an organosilicon-modified polyimide material with excellent performance through specific chemical reactions and control of conditions. This method not only improves the toughness, heat resistance, insulation and mechanical strength of the material, but also significantly improves the adhesion of PVDF through the synergistic effect with modified polyacrylonitrile (PAN), reduces the amount of PVDF used in lithium-ion batteries, thereby improving the energy density and cycle stability of the battery. Step S41: Preparation of prepolymer, this step forms a prepolymer containing isocyanate groups through the reaction of terminal amino silicone oil and diisocyanate. This step is the key starting point for preparing modified polyimide, and provides the necessary chemical basis for subsequent imidization reaction. Step S42: Synthesis of modified polyimide, in this step, the prepolymer further undergoes imidization reaction with anhydride monomers and diisocyanate to form organosilicon-modified polyimide. This material combines the flexibility of silicone with the heat resistance, insulation and mechanical strength of polyimide, providing a solid material basis for improving PVDF adhesion and battery performance. The compounding of modified polyacrylonitrile and modified polyimide is compounded in a specific ratio. The mechanical strength and chemical stability of modified polyacrylonitrile complement the heat resistance and insulation of modified polyimide, and act together on the PVDF surface to significantly improve the adhesion. Reduce the amount of PVDF. Due to the efficient adhesion of modified polyimide and modified polyacrylonitrile, the amount of PVDF used can be reduced while maintaining or even improving the adhesion performance, which helps to reduce the weight of the battery and increase the energy density. The addition of modified polyimide not only enhances the adhesion effect, but also helps to improve the cycle stability and overall performance of the battery due to its excellent heat resistance and mechanical strength. In summary, the preparation method of modified polyimide in this application and its synergistic effect with modified polyacrylonitrile provide an effective PVDF adhesion improvement solution for lithium-ion batteries, while optimizing the energy density and cycle stability of the battery.
[0014] Preferably, the diisocyanate is selected from one of hexamethylene diisocyanate and diphenylmethane diisocyanate; the anhydride monomer is selected from one of 4,4'-phenylenedioxydiphthalic anhydride and pyromellitic dianhydride; and the number average molecular weight of the amino-terminated silicone oil is 2000-6000.
[0015] Preferably, in step S41, the molar ratio of the amino-terminated silicone oil to the diisocyanate is 1:2.4-4.3.
[0016] Preferably, in step S42, the molar ratio of the prepolymer to the anhydride monomer is 0.18-0.40:1, and the molar ratio of the diisocyanate to the anhydride monomer is 0.25-0.76:1.
[0017] In a second aspect, the present application provides a method for preparing a PVDF adhesion enhancing promoter, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned PVDF adhesion enhancing promoter, comprising the following steps: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
[0018] In summary, the present application includes at least one of the following beneficial technical effects: 1. Significantly improve the adhesion of PVDF: Through scientific proportioning and composite technology, combined with the advantages of modified polyacrylonitrile (PAN) and modified polyimide (PI), the adhesion of PVDF is significantly improved. This improvement not only enhances the structural stability of the battery pole piece, but also improves the performance of the battery during the charging and discharging process.
[0019] 2. Reduce the amount of PVDF and increase energy density: Due to the efficient adhesion of modified polyimide and modified polyacrylonitrile, the amount of PVDF used can be reduced while maintaining or even improving the adhesion performance. This helps to reduce the weight of the battery and increase the energy density of the battery, thereby increasing the battery's endurance.
[0020] 3. Enhanced battery cycle stability: Modified polyimide, with its excellent heat resistance, insulation and mechanical strength, further enhances the adhesion effect as an auxiliary component and improves the overall performance of the battery. These properties help improve the stability and reliability of the battery in long-term cycle use.
[0021] 4. Improved processing performance: The modified polyimide is modified with a very flexible organic silicon segment (terminated amino silicone oil), and the resulting product has high toughness and good processing performance during pole piece processing. This makes the battery manufacturing process smoother and reduces production costs.
[0022] 5. Improve material compatibility and reactivity: The prepolymer generated by the reaction of amino-terminated silicone oil with diisocyanate and then the imidization reaction with anhydride monomers to obtain the organosilicon-modified polyimide effectively improves the compatibility and reactivity of the polysiloxane chain segment. This improvement not only improves the uniformity of the material, but also enhances its comprehensive performance.
[0023] 6. Synergy: The use of modified polyimide and modified polyacrylonitrile in a specific ratio and their synergy has achieved a significant improvement in PVD adhesion. This synergy not only optimizes the overall performance of the material, but also simplifies the production process and reduces costs.
[0024] 7. Convenient industrial production: The mature preparation process of modified PAN and modified PI ensures the large-scale production capacity of the accelerator, while proper cost control is conducive to market promotion and application. DETAILED DESCRIPTION
[0025] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0026] Preparation Example 1 Preparation of modified polyacrylonitrile In a four-necked reaction flask equipped with a stirrer, a thermometer, a reflux condenser, and a constant pressure dropping funnel, an emulsifier (sodium dodecyl sulfate, 0.5 g) and a solvent (H2O, 553.3 g) were added, and after stirring to completely dissolve, nitrogen was introduced, and then the first monomer (acrylonitrile, 90 g), the second monomer (butyl acrylate, 5 g), and the third monomer (lithium methacrylate, 5 g) were added for pre-emulsification for 0.5 h, and then under the protection of inert gas N2, the temperature was raised to a reaction temperature of 60°C, an initiator (ammonium persulfate, 0.4 g) was added dropwise for 1 h, and the reaction was continued at this temperature for 4 h. After the reaction was completed, an appropriate amount of ammonia water was added to neutralize to a pH of 7, and the product was filtered to obtain a polymer emulsion. The obtained polymer emulsion was spray-dried to obtain a solid powder, and the solid powder was washed with deionized water, dried, crushed, and sieved to prepare a modified acrylonitrile.
[0027] Preparation Example 2 Preparation of modified polyimide The preparation method of modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, 0.1 mol of amino-terminated silicone oil with a number average molecular weight of 2000, 0.25 mol of hexamethylene diisocyanate and 1500 g of N,N-dimethylformamide were mixed, and polymerization reaction was carried out at 30° C. for 6 hours to obtain a prepolymer; S62, while the prepolymer is being stirred, 0.1 mol of hexamethylene diisocyanate and 0.24 mol of 4,4'-phenylenedioxydiphthalic anhydride are added, the temperature is raised to 100° C. and the polymerization reaction is carried out for 8 hours to obtain a modified polyimide.
[0028] Preparation Example 3 Preparation of modified polyimide The same as Preparation Example 2, except that the number average molecular weight of the amino-terminated silicone oil is 6,000.
[0029] Preparation Example 4 Preparation of modified polyimide The same as Preparation Example 2, except that the number average molecular weight of the amino-terminated silicone oil is 4,000.
[0030] Preparation of Comparative Example 1 Preparation of Modified Polyimide The preparation method of modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, 0.1 mol of amino-terminated silicone oil with a number average molecular weight of 2000, 0.25 mol of hexamethylene diisocyanate and 1500 g of N,N-dimethylformamide were mixed, and polymerization reaction was carried out at 30° C. for 6 hours to obtain a prepolymer; S62, while the prepolymer is being stirred, 0.24 mol of 4,4'-dioxyphthalic anhydride is added, the temperature is raised to 100° C. and the polymerization reaction is carried out for 8 hours to obtain a modified polyimide.
[0031] Example 1 A PVDF adhesion promoter, the raw materials for preparation include: 0.3g modified polyacrylonitrile, 0.06g modified polyimide and 9.64g N,N-dimethylacetamide; the modified polyacrylonitrile is prepared in Preparation Example 1; the modified polyimide is prepared in Preparation Example 2; The preparation method of the above-mentioned PVDF adhesion enhancing promoter comprises the following steps: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
[0032] Example 2 A PVDF adhesion promoter, the raw materials for preparation include: 1g modified polyacrylonitrile, 2g modified polyimide and 7g N-methylpyrrolidone; the modified polyacrylonitrile is prepared in Preparation Example 1; the modified polyimide is prepared in Preparation Example 3; the preparation method of the above PVDF adhesion promoter includes the following steps: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
[0033] Example 3 A PVDF adhesion promoter, the raw materials for preparation include: 0.8g modified polyacrylonitrile, 0.8g modified polyimide and 84g N,N-dimethylformamide; the modified polyacrylonitrile is prepared in Preparation Example 1; the modified polyimide is prepared in Preparation Example 4; The preparation method of the above-mentioned PVDF adhesion enhancing promoter comprises the following steps: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
[0034] Example 4 A PVDF adhesion promoter, the raw materials for preparation include: 0.8g modified polyacrylonitrile, 0.48g modified polyimide and 8.72g N,N-dimethylformamide; the modified polyacrylonitrile is prepared in Preparation Example 1; the modified polyimide is prepared in Preparation Example 2; The preparation method of the above-mentioned PVDF adhesion enhancing promoter comprises the following steps: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
[0035] Comparative Example 1 The same as Example 4, except that: the modified polyimide is prepared in Preparation Comparative Example 1.
[0036] Performance testing 0.2 g of PVDF powder was added to the PVDF adhesion promoter prepared in Examples 1 to 4 and Comparative Example 1, respectively, and then ultrasonically stirred to ensure that the PVDF powder and the promoter solution were fully and evenly mixed to form the corresponding electrode binder. PVDF binder 5130 produced by Solvay Company of the United States was used as a reference example for comparison.
[0037] The binders prepared in the above-mentioned Examples 1 to 3 and Comparative Example 1 and the reference example PVDF binder 5130 were respectively used to prepare positive electrode sheets and lithium-ion batteries. The details are as follows: (1) Preparation of positive electrode sheets The active material lithium cobalt oxide, conductive carbon SP, and binder are dissolved in NMP in a weight ratio of 97:1:2, mixed evenly to prepare a positive electrode slurry, and the slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying, hot pressing, and slitting.
[0038] (2) Preparation of negative electrode sheets The active material graphite, conductive carbon SP, thickener sodium carboxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) are dissolved in deionized water at a weight ratio of 96.5:1:1:1.5, mixed evenly to prepare a negative electrode slurry, and the slurry is evenly coated on the negative electrode current collector copper foil, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0039] (3) Preparation of diaphragm Using PE porous polymer film as separator (4) Preparation of electrolyte Lithium hexafluorophosphate was dissolved in a carbonate solvent (ethylene carbonate, propylene carbonate, and ethyl methyl carbonate in a volume ratio of 2:2:2) to prepare a 1 mol / L electrolyte.
[0040] (5) Preparation of batteries The positive electrode sheet, separator and negative electrode sheet are wound in order to obtain a battery cell. The battery cell is packaged with an aluminum plastic film, baked at 85°C for 24 hours, and injected with electrolyte after dehydration. After vacuum packaging, shelving, formation, secondary sealing, shaping and other processes, a lithium-ion battery is obtained.
[0041] (6) Battery cycle test at room temperature The lithium-ion battery was charged to 4.35V at 1C constant current, then charged to a cut-off current of 0.02C at 4.35V, left for 5 minutes, and then discharged to 3.0V at 1C constant current, left for 5 minutes, and the first cycle discharge capacity was measured. After 500 cycles of charge / discharge, the 500th cycle discharge capacity was measured, and the 500th cycle capacity retention rate was calculated using the following formula: 500th cycle capacity retention rate (%) = (500th cycle discharge capacity / first cycle discharge capacity) × 100%. The specific results are shown in Table 1.
[0042] (7) Peel strength test: The prepared positive electrode sheet was cut into 10 cm × 2 cm strips and fixed to a 1 mm steel plate with double-sided tape on the current collector side. A transparent tape was pasted on the coating layer side. A 180° pulling peeling test was performed at a peeling speed of 100 mm / min using a universal electronic testing machine at 25°C. The peeling stress was recorded. The specific results are shown in Table 1.
[0043] Table 1 Performance test Analyzing the data in Table 1, we can see that: 1) The PVDF adhesion promoter prepared in Examples 1 to 4 cleverly combines the advantages of modified polyacrylonitrile (PAN) and modified polyimide (PI). Through scientific proportioning and composite technology, it achieves a significant improvement in the adhesion of PVDF, while effectively reducing the amount of PVDF used in lithium-ion batteries, thereby improving the battery's cycle stability.
[0044] 2) The performance comparison analysis of the PVDF adhesion promoter prepared in Example 4 and Example 3 shows that the mass ratio of modified polyacrylonitrile to modified polyimide is 1:0.6. Modified polyacrylonitrile (PAN) and modified polyimide (PI), as two polymer materials, play an important role in the preparation of PVDF adhesion promoter. By utilizing the synergistic effect between them and through reasonable proportioning, the advantages of the two materials can be complemented, thereby significantly improving the adhesion of PVDF and the cycle stability of the battery.
[0045] 3) The performance comparison analysis of the PVDF adhesion promoter prepared in Example 4 and Comparative Example 1 shows that in the process of preparing the modified polyimide, by further adding hexamethylene diisocyanate in the second step reaction for chain extension reaction, the bonding strength of the final binder in the application of the electrode positive plate and the cycle stability of the battery can be effectively improved.
[0046] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation methods of the present application can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the protection scope of the present application.
Claims
1. A PVDF adhesion promoter, characterized in that: The preparation raw materials include: modified polyacrylonitrile, modified polyimide and high-efficiency solvent, the mass ratio of the modified polyacrylonitrile to the modified polyimide is 1:0.2-2, and the high-efficiency solvent is selected from at least one of N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylformamide.
2. A PVDF adhesion promoter according to claim 1, characterized in that: The mass ratio of the modified polyacrylonitrile to the modified polyimide is 1:0.
6.
3. A PVDF adhesion promoter according to claim 1, characterized in that: The modified polyacrylonitrile is prepared from raw materials, calculated by weight: 80-90 parts of a first monomer, which is at least one of acrylonitrile and methacrylonitrile; 0-15 parts of a second monomer, which is at least one of an acrylate and a methacrylate monomer; 0-5 parts of a third monomer, which is a combination of one or more of an olefin acidic monomer, a sodium salt corresponding to an olefin acidic monomer, or a lithium salt corresponding to an olefin acidic monomer; and an emulsifier, deionized water, and an initiator.
4. A PVDF adhesion promoter according to claim 3, characterized in that: The second monomer is a combination of one or more of ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl methacrylate, isodecyl methacrylate, amyl acrylate, n-amyl methacrylate, isoamyl methacrylate, n-hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, lauryl acrylate, lauryl methacrylate, octadecyl acrylate, octadecyl methacrylate, methoxypolyethylene glycol methacrylate and ethoxyethyl acrylate; the third monomer is a combination of one or more of acrylic acid, sodium acrylate, lithium acrylate, methacrylic acid, sodium methacrylate, lithium methacrylate, β-acryloxypropionic acid, 2-acrylamide-2-methylpropane sulfonic acid, sodium allyl sulfonate, sodium vinyl sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
5. A PVDF adhesion promoter according to claim 3, characterized in that: The preparation method of the modified polyacrylonitrile comprises the following steps: (1) Pre-emulsification: After the first monomer, the second monomer and the third monomer are uniformly mixed, an emulsifier and deionized water are added for pre-emulsification to obtain a mixed emulsion; (2) heating the pre-emulsified mixed emulsion in step (1) to the reaction temperature and stirring the reaction, adding the initiator dropwise for 1 hour, and keeping the temperature for 4 hours to obtain a preliminary emulsion; (3) filtering, neutralizing and cooling the preliminary emulsion obtained in step (2) to obtain a polymer emulsion; (4) drying the polymer emulsion obtained in step (3) to obtain a solid powder; (5) The solid powder obtained in step (4) is washed, purified, dried, and sieved to obtain modified polyacrylonitrile.
6. A PVDF adhesion promoter according to claim 1, characterized in that: The preparation method of the modified polyimide comprises the following preparation steps: S61. Under nitrogen protection, amino-terminated silicone oil, diisocyanate and N,N-dimethylformamide are mixed, and polymerization reaction is carried out at 25-60° C. for 4-10 hours to obtain a prepolymer; S62, polymerizing the prepolymer with anhydride monomer and diisocyanate at 90-100° C. for 6-12 hours to obtain.
7. A PVDF adhesion promoter according to claim 6, characterized in that: The diisocyanate is selected from one of hexamethylene diisocyanate and diphenylmethane diisocyanate; the anhydride monomer is selected from one of 4,4'-phenylenedioxydiphthalic anhydride and pyromellitic dianhydride; and the number average molecular weight of the amino-terminated silicone oil is 2000-6000.
8. A PVDF adhesion promoter according to claim 6, characterized in that: In step S61, the terminal amino silicone oil and diisocyanate are mixed in a molar ratio of 1:2.4-4.
3.
9. A PVDF adhesion promoter according to claim 6, characterized in that: In step S62, the molar ratio of the prepolymer to the anhydride monomer is 0.18-0.40:1, and the molar ratio of the diisocyanate to the anhydride monomer is 0.25-0.76:
1.
10. A method for preparing a PVDF adhesion promoter as claimed in any one of claims 1 to 9, characterized in that: The following steps are involved: According to the formula dosage, the modified acrylonitrile and the modified polyimide are dissolved in a high-efficiency solvent in proportion and fully mixed to obtain a PVDF adhesion enhancing promoter.
Citation Information
Cited By
Production method of control cable with double-layer shielding structure
CN120261066A